Studi Populasi Burung Wader (Charadriiformes) pada Akhir Musim Migrasi di Semenanjung Sembilang Banyuasin, Sumatera Selatan - Kasturi Wamepa; Agus Purwoko; Mustafa Kamal (Jurnal Penelitian Sains, 2018)
Waders migrate to maintain survival, to find new food sources and avoid extreme environmental changes. Waders population in a location varies according to environmental conditions. The study was con-ducted using the point count method. The observation time of each location is 30 minutes with repetition 3 times. There are four observation locations, namely Bungin River Estuary, Solok Buntu Estuary, Barong Kecil River Estuary, and Siput River Estuary. Data analysis technique uses correlation analysis. The results showed the number of wader birds at the end of the season migration in the Siput River Estuary was 886 individuals, while the Barong Kecil River Estuary was 536 individuals, Bungin River Estuary 140 individuals, and Solok Buntu Estuary 105 individuals. Tringa totanus, Limosa laponica, and Numenius arquata can be found at each observation location. Wader birds population found correlated with macrozoobenthos density had a correla-tion coefficient of 0.73.